Improving the Al-Qur’an Recitation Skills of Children at Nurul Bahar Mosque’ TPA, Sungai Pisang Village through a Mentoring Program - Khatimah, Husnil; Putri, Respika Aprilia; Dwi Salbilah, Shella (Indonesian Journal of Community Services Cel, 2023)
Children in Sungai Pisang Village have a low interest in Al-Qur’an recitation because many of them prefer to play rather than learn the Al-Qu’ran. One of the factors causing the low interest of children in Sungai Pisang Village in reciting the Al-Qur’an is the shortage of teachers or facilitators so that the children feel bored waiting for their turn to recite the Al-Qur’an. For that reason, this community services activity aims to improve the children's ability to recite the Al-Qur’an in Sungai Pisang Village by participating in teaching the Al-Qur’an recitation. The methods used were observation and face-to-face mentoring. Observation was conducted by visiting Al-Qur’an learning center (TPA) at Nurul Bahar Mosque and collecting information from teachers regarding the children's interest in reciting the Al-Qur’an in this place. The activity implementation comprised reading and reciting hijaiyah letters, learning the length and shortness of recitation, reading short passage, and didikan subuh (activities to educate children about fundamental virtues of Islam). Partners in this activity were teachers and children who recite the Al-Qur’an in Sungai Pisang Village. The results of this activity can help teachers to improve the learning process of Al-Qur’an recitation for children at Nurul Bahar Mosque’ TPA, which is indicated by the number of students who have improved their ability to read and recite the Al-Qur’an, namely 35 children or 70% of total participants.